PERAN E-BANKING TERHADAP KEPUASAN DAN LOYALITAS NASABAH PT. BANK CENTRAL ASIA Tbk. - Hika Rochmah (2021)
With the development of technology, the banking industry innovates digital banking services by presenting the E-Banking system. E-Banking provides various benefits for customers, banks and authorities. Based on the results of the survey, the authors show that customers, especially at PT. Bank Central Asia Tbk., give a positive response to the use of E-Banking services which provide various conveniences for transactions such as transfers, bill payments, m-commerce, voucher purchases and so on. In addition, PT. Bank Central Asia Tbk. also provides a good level of security for its E-Banking system for the convenience of customers. In terms of convenience, comfort and security felt by customers, it gives a high value to the performance and services provided by PT. Bank Central Asia Tbk.. The customer's positive response produces a satisfaction that creates customer loyalty. Therefore, the role of E-Banking is one of the alternatives for Bank BCA in improving and maintaining customer satisfaction and loyalty through performance and innovation in digital banking services.